Exploring the supportive care needs for people with chronic kidney failure undergoing hemodyalisis: A qualitative study - Al Harbi, Fahd; Bin Khalid, Layla; Al Qadhi, Aisha (STIKes Al-Ma'arif Baturaja, 2025)
Background: Chronic kidney failure requiring hemodialysis is a growing health burden in Saudi Arabia, with significant physical, psychological, social, and cultural implications. While clinical outcomes are well-documented, patients’ supportive care needs remain underexplored. Objective: This study aimed to explore the supportive care needs of individuals with chronic kidney failure undergoing hemodialysis in Saudi Arabia. Methods: A qualitative descriptive design was applied. Sixteen patients receiving maintenance hemodialysis for at least six months were purposively recruited. Data were collected through semi-structured, in-depth interviews and analyzed using Braun and Clarke’s six-step thematic framework. Results: Four overarching themes emerged: (1) the impact of fatigue and the need for fatigue self-management, (2) the necessity of family and social support, (3) the importance of psychological and emotional support from healthcare professionals, and (4) changes in role performance and the need for adaptation. Patients reported profound physical exhaustion, psychosocial distress, dependence on family, and disruption of daily roles. Empathy, cultural sensitivity, and supportive interventions were identified as critical to improving patient well-being. Conclusion: Hemodialysis patients in Saudi Arabia face multidimensional supportive care needs that extend beyond clinical management. Addressing fatigue, enhancing family and social involvement, fostering psychological support, and facilitating adaptation to role changes are essential to delivering holistic, patient-centered care. Culturally sensitive strategies should be integrated into routine practice to optimize quality of life and health outcomes.